The burn patient as a time-dependent entity: an evidence-based practical guide. - O. A, Romero - Arguello; D. E, Meraz - Brenes; J.F, López - Gonzáles; Moreno R.,, Iribarren; González - Aboytes , J.E; Medina – Preciado , J. D; A. C., Cepeda - Nieto (Revista de Ciencias Médicas Torreón, 2026)
The management of burn patients is time-critical; initial caredirectly influences the progression of tissue damage, proteincoagulation, circulatory disturbances, and necrosis. Keyinitial interventions include primary assessment using theABCDE approach, early analgesia, fluid resuscitation,evaluation of injury characteristics and extent, and criteria fortimely referral to specialized centers. Thermal burns are themost prevalent (86%), followed by electrical (4%) andchemical (3%) burns, with high global annual morbidity andmortality (11 million affected; 180,000 deaths). It isproposed, practical algorithm is proposed to standardizeinitial management, optimize decision-making, and improveclinical outcomes for burn patients during the initial carephase.
Keywords: Burns; Prehospital Care; Initial Management; Palabras Clave: Quemaduras; atención prehospitalaria; Inhalation Injury; Fluid Resuscitation; Emergency Care.